GAMBARAN FAKTOR-FAKTOR YANG MEMENGARUHI KADAR HB PADA PASIEN HEMODIALISA - Ainul Adillah Rusdiana; Erna Melastuti; Ahmad Ihklasul Amal (Rena Cipta Mandiri, 2026)
Patients with chronic kidney failure undergoing hemodialysis often experience a decrease in hemoglobin levels as an indication of anemia, which is greatly influenced by various factors such as nutritional status, age, gender, and family history. This study aims to identify the factors affecting hemoglobin levels in hemodialysis patients at RSUD Dr. Loekmono Hadi Kudus. This study used a descriptive analytical method with a quantitative descriptive approach. A sample of 129 patients was taken using purposive sampling. Data were collected through observation and medical records, then analyzed using correlation and significance statistical tests. The analysis results showed that malnutrition has a significant relationship with hemoglobin levels (p < 0.05) using the Chi-square test, while factors such as age, gender, and family history did not show a significant relationship. Malnutrition impacts low hemoglobin levels, potentially worsening the patient's condition. Malnutrition is a significant factor affecting hemoglobin levels in hemodialysis patients. Therefore, special attention to the nutritional status of patients is very important to maintain hemoglobin levels and improve the quality of life of hemodialysis patients.